2022
DOI: 10.1097/bpo.0000000000002140
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Series of Deformity Correction Using Guided Growth in the Setting of Osteogenesis Imperfecta

Abstract: Background: The mainstay of deformity correction and fracture prevention for patients with osteogenesis imperfecta (OI) includes osteotomies and intramedullary rodding. Guided growth, described in the setting of skeletal dysplasias, offers a less invasive means of deformity correction. We report a multicenter case series of guided growth procedures in the setting of OI. Methods: We retrospectively reviewed patients with OI at three institutions from April 2012 to April 2019: 18 patients underwent guided growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…In a retrospective cohort study of 783 patients with OI, Yang et al 70 found that in the treatment of long bone fractures and deformities, intramedullary telescoping rods showed the lowest revision rate and longest implant survival period compared with other fixation techniques, confirming earlier results of a meta-analysis. 71 Franzone et al 72 demonstrated in a multicenter study that GG procedure can be effective in patients with OI. Cyclic intravenous therapy with bisphosphonates has become an established part of the treatment of moderate to severe OI.…”
Section: X-linked Hypophosphatemia and Osteogenesis Imperfectamentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study of 783 patients with OI, Yang et al 70 found that in the treatment of long bone fractures and deformities, intramedullary telescoping rods showed the lowest revision rate and longest implant survival period compared with other fixation techniques, confirming earlier results of a meta-analysis. 71 Franzone et al 72 demonstrated in a multicenter study that GG procedure can be effective in patients with OI. Cyclic intravenous therapy with bisphosphonates has become an established part of the treatment of moderate to severe OI.…”
Section: X-linked Hypophosphatemia and Osteogenesis Imperfectamentioning
confidence: 99%
“…Franzone et al 72 demonstrated in a multicenter study that GG procedure can be effective in patients with OI. Cyclic intravenous therapy with bisphosphonates has become an established part of the treatment of moderate to severe OI.…”
Section: X-linked Hypophosphatemia and Osteogenesis Imperfectamentioning
confidence: 99%
“…Franzone et al highlighted the role of guided growth surgery in correcting angular deformities in a case series involving 18 patients with osteogenesis imperfecta 47 . Harmer et al described a technique for anterior distal femoral hemiepiphysiodesis using percutaneous cannulated screws to correct knee flexion contractures in patients with cerebral palsy 48 .…”
Section: Guided Growthmentioning
confidence: 99%
“…Lösung der eingebrachten Schraube beobachtet. In Anbetracht der mit der OI verbundenen Kleinwüchsigkeit sollte die Durchführung eines wachstumslenkenden Verfahrens in einem tendenziell jüngeren Alter erwogen werden, da dieses Prinzip genügend Zeit für eine entsprechende Korrektur benötigt [32].…”
Section: Temporäre Epiphysiodeseunclassified